Theoretical foundations of buffer stock saving - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2004)
Buffer-stock versions of the dynamic stochastic optimizing model of saving are now standard in the consumption literature. This paper builds theoretical foundations for rigorous understanding of the main characteristics of buffer stock models, including the existence of a target level of wealth and the proposition that aggregate consumption growth equals aggregate income growth in a small open economy populated by buffer stock consumers.
Keywords: D81; D91; E21; 330; Precautionary saving; buffer stock saving; marginal propensity to consume; permanent income hypothesis; Sparen; Dynamische Optimierung; Gesamtwirtschaftlicher Konsum; Kleines-offenes-Land